The Use of Euphemism on the Talk Show â€œSeteru Luhut vs Harisâ€ - Hasibuan, Alika Sandra; Tausya, Resi Syahrani; Sinaga, Lusiana (Tradition and Modernity of Humanity, 2023)
This study aims to describe the use of the types and meanings of any euphemisms contained in Najwa Shihab's talk show entitled "Seteru Luhut vs Haris on Mining in Papua". This study uses a qualitative descriptive method with a semantic approach. The data source in this study was a YouTube rebroadcast of Najwa Shihab's talk show entitled "Seteru Luhut vs Haris on Mining in Papua". The data analysis technique used is data reduction, data presentation, verification and conclusion. The results showed that there were seven types of euphemism, namely: flippant type, remodelling type, figurative expression type, circumlocutionary type, term borrowing type and jargon type. In addition, two euphemistic meanings are contained in the video: a conceptual meaning which contains utterances or messages based on the concept and associative meaning, which contains meanings that do not refer to objects, body parts, and events.